The Body of Christ ad hoc? Changes in the Church of Sweden’s Eucharistic celebrations after the Covid-19-pandemic (Nordic Journal of Practical Theology, 2025)
During the Covid-19-pandemic, the Church of Sweden (CofS) adjusted its eucharistic practices, and congregations practiced a variety of adjustments. These adjustments were motivated and problematized in relation to community, often referencing a metaphor crucial in the development of CofS theology during the 20th Century: “the body of Christ.” Scholars also speculated on how these adjustments could affect theology in the long run. This article aims to describe the state of these practices one year after the pandemic, analyzing whether the various adjustments remain. By comparing two nationwide surveys from 2020 and 2023 within the CofS, the article shows that while some adjustments have declined, many remain. The theological implications of these changes are discussed in relation to the metaphor of the body of Christ, drawing on how the metaphor has been developed by theologians reflecting on the HIV/AIDS epidemic in the African context.
Keywords: Eucharist; Holy communion; Church of Sweden; Covid-19; Pandemic; Body of Christ